Biliary Drainage Method and Temporal Trends in Patients Admitted with Cholangitis: A National Audit - Julia McNabb-Baltar; Quoc-Dien Trinh; Alan N Barkun (Canadian Journal of Gastroenterology)
BACKGROUND: In patients presenting with ascending cholangitis, better outcomes are reported in those undergoing endoscopic retrograde cholangiopancreatography (ERCP) compared with surgical drainage.